2016
DOI: 10.1021/acs.jpcb.6b08853
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Dimethyldodecylamine Oxide and Its Mixtures with Triton X-100 at the Hydrophilic Silica/Water Interface Studied Using Total Internal Reflection Raman Spectroscopy

Abstract: Adsorption of dimethyldodecylamine oxide (DDAO) and its mixtures with Triton X-100 (TX-100) at the hydrophilic silica/water interface has been studied using total internal reflection (TIR) Raman spectroscopy and target factor analysis (TFA). The use of a linear vibrational spectroscopic technique helps obtain information on molecular behavior, adsorbed amount, and conformational order of surfactant molecules at the interface. The results obtained from polarized Raman measurements of pure DDAO show insignifican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Although neutron reflectivity is not capable of resolving the nature of the structures at the interface of these films spun onto a silicon substrate due to the similar SLD of the silicon oxide and the PVA containing this volume fraction of deuterated surfactant, there has been substantial evidence for the formation of structures on solution-substrate interfaces. When reflectivity data for a PVA/DDAO film was fitted with a 4-layer model, to include an additional surfactant-rich layer adjacent to the substrate, the thickness of the interfacial layer was found to be 13 ± 10 Å, which could correspond to a number of different structures, which have been probed theoretically and experimentally. The significant uncertainty in this value is a result of the difficulty in resolving the interfacial surfactant from the SiO x (25 ± 15 Å). It was previously reported that treating structured surfactant films as a bilayer generally results in a good fit to reflectivity data .…”
Section: Discussionmentioning
confidence: 99%
“…Although neutron reflectivity is not capable of resolving the nature of the structures at the interface of these films spun onto a silicon substrate due to the similar SLD of the silicon oxide and the PVA containing this volume fraction of deuterated surfactant, there has been substantial evidence for the formation of structures on solution-substrate interfaces. When reflectivity data for a PVA/DDAO film was fitted with a 4-layer model, to include an additional surfactant-rich layer adjacent to the substrate, the thickness of the interfacial layer was found to be 13 ± 10 Å, which could correspond to a number of different structures, which have been probed theoretically and experimentally. The significant uncertainty in this value is a result of the difficulty in resolving the interfacial surfactant from the SiO x (25 ± 15 Å). It was previously reported that treating structured surfactant films as a bilayer generally results in a good fit to reflectivity data .…”
Section: Discussionmentioning
confidence: 99%
“…In substance analysis, the adsorption of dimethyldodecylamine oxide (DDAO) and its mixtures with Triton X‐100 (TX‐100) at the hydrophilic silica/water interface has been studied using total internal reflection (TIR) Raman spectroscopy and target factor analysis (TFA). [ 64 ] When studying the influence of pressure and environment on the Raman spectra of methane, carbon monoxide, carbon dioxide, and hydrogen, a method was proposed to predict the positions of these molecule peaks. [ 65 ] In recent years, Raman spectroscopy has been proven to qualitatively and quantitatively analyze xylene isomers and their mixtures.…”
Section: Applicationmentioning
confidence: 99%
“…Chemometrics and analytical techniques, such as partial least-squares, principal component analysis, multivariate analysis, and factor analysis, have been utilized in spectral and image analysis in many spectroscopic techniques. Factor analysis (FA) is a statistical method that uses mathematical procedures to investigate whether some observed variables are linearly related to some smaller number of unobservable factors. The application of FA in chemistry has been pioneered by Malinowski in the 1980s .…”
Section: Introductionmentioning
confidence: 99%